A General Method for the Analysis of Hourly Heights of Tide - Murray, M. T. (The International Hydrographic Review, 2015)
A number of methods have been devised (references 1-4) for the analysis of a sequence of observations of hourly heights of tide in terms of a suitable theoretical model, using a digital electronic computer. These methods all contain restrictions or approximations of one form or another. These are sometimes due to the use on a computer of a method originally designed so that it would be a feasible calculation using desk calculating-machines; sometimes the restrictions applied are due to the limited size or speed of the computer used. The use of large modern computers (such machines as Ferranti ATLAS, IBM 7090, English Electric KDF9 come to mind) means that most, if not all, of these restrictions are no longer necessary, and that accurate analyses can be economically produced using quite general and unrestricted methods. It is the author’s intention to discuss in this paper the characteristics required of a flexible scheme of analysis, the methods by which the results might be obtained, and the way in which the resulting computer program would be used.